UJI KUALITATIF BERAS KRAYAN DAN POTENSI PENERAPANNYA PADA LEMBAR KERJA SISWA (LKS) SEBAGAI BAHAN AJAR SAINS BIOLOGIUJI KUALITATIF BERAS KRAYAN DAN POTENSI PENERAPANNYA PADA LEMBAR KERJA SISWA (LKS) SEBAGAI BAHAN AJAR SAINS BIOLOGI - eikke eikke; fatmawati fatmawati; nursia nursia (Program Studi Pendidikan Biologi Universitas Borneo Tarakan, 2023)
This study used both qualitative and quantitative methods to conduct descriptive research. Throught qualitative test and documentation, this study intented to evaluate the content of carbs (reduced sugar) in krayan rice, specifically white Adan, red Adan, black Adan, Tuan Sia, Tuan Boda, Air, Abang, Abang, Kelabit, and Nanung. The Fehling, Benedict. And Iodine test was the qualitative test method employed. Carbohydrates were one of the most important nutrients for human health because they served a variety of tasks, including delivering energy to body cells, particularly brain cells and the central nervous system, which required blood glucose intake. The results of the study on the krayan rice sample revealed a carbohydrate content with the type of decreasing sugar as demonstrated by a shift in color to brick red, but with varying color intensities, concentrated color such as Nanung rice, Adan black rice, Kelabit rice, and Abang rice. Positive test for starch (polysaccharide) carbohydrates, namely Amylose, as evidenced by a blue color change in the sample. With a validation score of 96% and inclusion in the valid evaluation criteria, the result of the qualitative test of krayan rice were poured into the form of students Worksheets (LKS) as Biology Science Teaching Materials for class VIII students, especially in natural science (IPA) subject.Â Keybords: Carbohydrates, Krayan rice, LKSÂ